Rational Design Oxygen and Sulfur Dual-Doped 3D Hierarchical Porous Carbons for High-Performance Lithium-Sulfur Batteries. Issue 2 (3rd January 2018) - Cao, Zhaoxia; Zhang, Ruirui; Shi, Mengjiao; Zhu, Guangshuang; Yang, Mingguo; Zhang, Huishuang; Qiao, Yun; Yang, Shuting
Abstract : Oxygen and sulfur dual-doped 3D interconnected hierarchical porous carbons (HPCs) were synthesized via pyrolysis followed by chemical activation of natural alginate. The results showed that both an appropriate poristy and high level of S doping lead to the excellent electrochemical performance. The optimal HPC-Na-900/S composite exhibited outstanding electrochemical performance as cathode materials for Li-S batteries. Specially, the electrochemical performances of the resultant HPC/S composites change randomly with the surface area, pore volume except porosity and surface chemistry under the testing conditions. The porosity plays a more important role than surface area as well as pore volume which are the crucial parameters in designing of porous carbon, and only the ratio of these hierarchical pores reaches a specific range, the best battery performance can be achieved. The introduction of heteroatom are also key factors that determines the performance of lithium-sulfur batteries. This insight into the relation of microstructure and surface chemistry with battery performance can help to guide better understand and rationally design porous carbon hosts.